An efficient Bouc & Wen approach for seismic analysis of masonry tower - Luca Facchini; Michele Betti (Fracture and Structural Integrity)
The assessment of existing masonry towers under exceptional loads, such as earthquake loads, requires reliable, expedite and efficient methods of analysis. These approaches should take into account both the randomness that affects the masonry properties (in some cases also the distribution of the elastic parameters) and, of course, the nonlinear behavior of masonry. Considering the need of simplified but effective methods to assess the seismic response of such structures, the paper proposes an efficient approach for seismic assessment of masonry towers assuming the material properties as a stochastic field. As a prototype of masonry towers a cantilever beam is analyzed assuming that the first modal shape governs the structural motion. With this hypothesis a nonlinear hysteretic Bouc & Wen model is employed to reproduce the system response which is subsequently employed to evaluate the response bounds. The results of the simplified approach are compared with the results of a finite element model to show the effectiveness of the method.